Respuesta :

[tex]\bf a^{\frac{{ n}}{{ m}}} \implies \sqrt[{ m}]{a^{ n}} \qquad \qquad \sqrt[{ m}]{a^{ n}}\implies a^{\frac{{ n}}{{ m}}} \\\\\\ \left.\qquad \qquad \right.\textit{negative exponents}\\\\ a^{-{ n}} \implies \cfrac{1}{a^{ n}} \qquad \qquad \cfrac{1}{a^{ n}}\implies a^{-{ n}} \qquad \qquad a^{{{ n}}}\implies \cfrac{1}{a^{-{{ n}}}}\\\\ -------------------------------[/tex]

[tex]\bf \left( g^{\frac{2}{3}} \right)^2\cdot g^{-2}\implies \left( g^{\frac{2}{3}} \right)^2\cdot g^{-2}\implies \left( g^{\frac{2}{3}\cdot 2} \right)\cdot g^{-2}\implies g^{\frac{4}{3}}\cdot g^{-2} \\\\\\ g^{\frac{4}{3}-2}\implies g^{\frac{4-6}{3}}\implies g^{\frac{-2}{3}}\implies \cfrac{1}{g^{\frac{2}{3}}}\implies \cfrac{1}{\sqrt[3]{g^2}}[/tex]